Variations in strength-speed-power performance across the season: do true changes occur in elite rugby players? - Loturco, Irineu; Bishop, Chris; Zabaloy, Santiago; Moura, Túlio B.M.A.; Ramos, Maurício S.; Pereira, Lucas A.; McGuigan, Michael (Biology of Sport, 2024)
This study aimed to determine, through the use of a highly sensitive statistical tool, whether real changes in performance were present; and compare the rates of meaningful variations in strength, speed, and power parameters at different time-points during the competitive season in national team rugby players. Thirtytwo players were assessed 5 times across the season using the following tests: squat jump and countermovement jump tests; 30-m sprint velocity; and one-repetition maximum (1RM) in the half-squat and bench-press exercises. A repeated measures analysis of variance was conducted to test for differences between successive time-points. Individual coefficients of variation values were used to set target scores for post measurements and examine whether changes in performance parameters were greater than the natural test variance, thus providing an indication of whether “true changes” occurred. No significant changes were detected in the vertical jump height, 1RM measures, and sprint velocity and momentum throughout the 11-month period ( P > 0.05). True changes occurred much more frequently for strength-power measures than for sprint velocity and momentum. Elite rugby union players did not exhibit significant variations in neuromuscular performance across the competitive period, when a group-based analysis was conducted. However, at the individual level, “true changes” in strength-power- (but not in speed-) related qualities were consistently observed over the competitive season.